Let $p(x)=x^n+\dots$ monic polynomial of degree $n$ and $U_n$ n-th Chebyshev polynomial of second kind.Then it holds $$ \|p\|\geq\|\dfrac{1}{2^{n}}U_n\|=\dfrac{1}{2^{n-1}}$$ where $\|f\|=\int_1^{-1}|f(x)|dx$.

I found this theorem but without proof.Can someone give me a reference or prove it here?


Note that $U_n(x)=\frac {\sin (n+1)\theta}{\sin \theta}, x=\cos \theta$, so in particular the degree of $U_n$ is $n$ and its leading coefficient is $2^n$ since $\sin ((n+1)\theta)+\sin ((n-1)\theta)=2\cos \theta \sin (n\theta)$, so $U_n(x)=2xU_{n-1}(x)-U_{n-2}(x), n \ge 2, U_0(x)=1, U_1(x)=2x$

Let $s(x)=\frac{x}{|x|}, x \ne 0, s(0)=0$ be the sign function for real $x$. We note that $f(x)s(f(x))=|f(x)| \ge f(x)s(g(x))$ for any pair of real functions $f,g$ as $|f(x)| \ge \pm f(x)$.

Lemma: $\int_{-1}^1U_k(x)s(U_n(x))dx=0, k=0,..,n-1$

Assuming the lemma is proved, it then implies (if $p$ has real coefficients, while otherwise, we apply it to $\Re p$ which is a monic polynomial of the same degree with real coefficients and $|p(x)| \ge |\Re p(x)|$) that

$\int_{-1}^1(p(x)-2^{-n}U_n(x))s(U_n(x))=0$ since $p(x)-2^{-n}U_n(x)$ has degree at most $n-1$ so it is a linear combination of $U_0, U_1,..U_{n-1}$

But now as $|p(x)| =p(x)s(p(x)) \ge p(x)s(U_n(x))$ as noted, we integrate and get:

$\int_{-1}^1|p(x)|dx \ge \int_{-1}^1p(x)s(U_n(x))dx=\int_{-1}^12^{-n}U_n(x)s(U_n(x))dx=2^{-n}\int_{-1}^1|U_n(x)|dx$ so we only need to prove the lemma and compute $\int_{-1}^1|U_n(x)|dx$ to finish

First the Lemma:

Remembering the definition and using $x=\cos \theta, 0 \le \theta \le \pi, \sin \theta \ge 0$:

$\int_{-1}^1U_k(x)s(U_n(x))dx=\int_0^{\pi}(\sin (k+1)\theta)s(\sin (n+1)\theta)d\theta$ and since the integrand is even, it is enough to prove $\int_{-\pi}^{\pi}(\sin (k+1)\theta)s(\sin (n+1)\theta)d\theta=0$ as that is twice our integral.

We use the usual Fourier trick and notice that if we let

$I_k=\int_{-\pi}^{\pi}e^{ik\theta}s(\sin (n+1)\theta)d\theta=\int_{-\pi+a}^{\pi+a}e^{ik(\theta+a)}s(\sin (n+1)(\theta+a))d\theta=\int_{-\pi}^{\pi}e^{ik(\theta+a)}s(\sin (n+1)(\theta+a))d\theta =e^{ika}\int_{-\pi}^{\pi}e^{ik\theta}s(\sin (n+1)(\theta+a))d\theta$

with first equality by substitution, second by periodicity.

But now for $a=\frac{\pi}{n+1}$ we clearly have $s(\sin (n+1)(\theta+a))=-s(\sin (n+1)\theta)$, so $I_k=-e^{i\frac{k\pi}{n+1}}I_k$, or $I_k=0, 1 \le k \le n$ and the lemma follows by noticing that our original integral is the imaginary part of $I_k$

For the last part:

$\int_{-1}^1|U_n(x)|dx=\int_0^{\pi}|\sin (n+1)\theta|d\theta=\frac{1}{n+1}\int_0^{(n+1)\pi}|\sin \theta|d\theta=\int_0^{\pi}|\sin \theta|d\theta=2$ so we are done (again we use substitution, periodicity and then $|\sin \theta|=\sin \theta, 0 \le \theta \le \pi$)

Note that the proof shows that we can have equality iff $p=2^{-n}U_n$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.